Design and Implementation mDPBL Teaching Approach to Improve Students' Creative Thinking Skill - Yupie Kusumawati; Sri Winarno; M. Hafidz Ariansyah; Esmi Nur Fitri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
The majority of learning in Universities is adopting the Direct Instructional (DI) approach. The DI approach is a lecturer-centered approach. Howover, this approach tends to be boring for the students as it is very tedious and dominated by the lecturer. Moreover, this approach limits students in developing the habit of problem-solving and creative thinking in learning processes. Therefore, it is very important to develop a new innovative approach in teaching activity that gives students more opportunities to be involved in the learning process. Direct Problem-Based Learning with the utilisation of Multimedia (mDPBL) is developed as an alternative teaching approach to eliminate the disadvantages, especially in the limitations in students' creative thinking.This research measures students’ creative thinking skills after being taught using mDPBL approach. This research uses quasi-experimental method. 276 students involved in this research. The result of the measurement shows that the students’ controlled group has an average score of 18.014 while the latter, the experimental group has an average score of 19.669. Based on the t-test analysis conducted in both groups, they have shown a difference of 1.655 in average score. Therefore, there is an indication that the mDPBL approach contributes to improving students’ creative thinking skills.